Optimization of Phytoremediation of Industrial Wastewater with Water Hyacinth Plant using Response Surface Methodology - Lee Kar Chun (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To produce baseline value of heavy metal content in the water hyacinth obtained from uncontrolled environment. To determine the parametric effect of initial heavy metal concentration pH and contact time, towards heavy metal uptake capacity and pH changes in wastewater. To optimize the process of removal of PTEs from simulated wastewater using Response Surface Methodology.